Những câu hỏi liên quan
NT
Xem chi tiết
FD
4 tháng 11 2018 lúc 9:57

Tìm x, biết:

a, \(\dfrac{5}{2}:\dfrac{x}{6}=5:0,2\)

\(\dfrac{5}{2}.\dfrac{6}{x}=\dfrac{5}{0,2}=\dfrac{25}{1}\)

\(\dfrac{5}{1}.\dfrac{3}{x}=\dfrac{25}{1}\)

\(\dfrac{3}{x}=\dfrac{25}{1}.\dfrac{1}{5}\)

\(\dfrac{3}{x}=\dfrac{5.1}{1.1}=5\)

\(3:x=5\)

\(x=3:5=0,6\)

Vậy x = 0,6

Bình luận (0)
NT
17 tháng 11 2022 lúc 13:00

b: =>11/4*x=22/7:1/100=22/7*100=2200/7

=>x=2200/7:11/4=800/7

a: \(\Leftrightarrow\dfrac{5}{2}\cdot\dfrac{6}{x}=5\cdot5=25\)

=>30/2x=25

=>2x=6/5

=>x=3/5

Bình luận (0)
JC
Xem chi tiết
LL
Xem chi tiết
NH
27 tháng 8 2023 lúc 11:22

a, - \(\dfrac{2}{5}\) + \(\dfrac{4}{5}\).\(x\) = \(\dfrac{3}{5}\)

               \(\dfrac{4}{5}\).\(x\) = \(\dfrac{3}{5}\)\(\dfrac{2}{5}\)

                 \(\dfrac{4}{5}\).\(x\) = 1

                      \(x\) = \(\dfrac{5}{4}\)

b, - \(\dfrac{3}{7}\) - \(\dfrac{4}{7}\)\(x\) = \(\dfrac{2}{5}\)

              \(\dfrac{4}{7}\)\(x\) = - \(\dfrac{3}{7}\) - \(\dfrac{2}{5}\)

                \(\dfrac{4}{7}\)\(x\) = - \(\dfrac{29}{35}\)

                  \(x\) = \(\dfrac{4}{7}\): (- \(\dfrac{29}{35}\) )

                  \(x\) = - \(\dfrac{20}{29}\)

Bình luận (0)
NH
27 tháng 8 2023 lúc 11:24

c, \(\dfrac{4}{7}\).\(x\) + \(\dfrac{2}{3}\) = - \(\dfrac{1}{5}\)

     \(\dfrac{4}{7}\).\(x\)         = -\(\dfrac{1}{5}\) - \(\dfrac{2}{3}\)

      \(\dfrac{4}{7}\).\(x\)       = - \(\dfrac{13}{15}\)

           \(x\)     = - \(\dfrac{13}{15}\)\(\dfrac{4}{7}\)

            \(x\)    = - \(\dfrac{91}{60}\)

Bình luận (0)
NH
27 tháng 8 2023 lúc 11:26

d, \(\dfrac{5}{7}\)\(x\) - 1 = \(\dfrac{2}{3}\)

     \(\dfrac{5}{7}\)\(x\)     = \(\dfrac{2}{3}\)+ 1

       \(\dfrac{5}{7}\)\(x\)   = \(\dfrac{5}{3}\)

              \(x\)  = \(\dfrac{5}{7}\)\(\dfrac{5}{3}\)

               \(x\) = \(\dfrac{3}{7}\)

Bình luận (0)
MT
Xem chi tiết
H24
16 tháng 10 2023 lúc 19:41

`3/5 : x =1/3 +1/2`

` 3/5 : x= 2/6 +3/6`

` 3/5 : x= 5/6`

` x= 3/5 : 5/6`

` x= 3/5 xx 6/5`

` x= 18/25`

__

`x: 7/15 =2`

` x= 2xx 7/15`

` x= 14/15`

__

`x-3/2=11/4-5/4`

`x-3/2= 6/4`

`x= 3/2 +3/2`

`x= 6/2`

`x=3`

__

`x+5/4 = 3/2+7/12`

`x+5/4 = 18/12+7/12`

`x+5/4 = 25/12`

`x= 25/12-5/4`

`x= 25/12- 15/12`

`x= 10/12`

`x= 5/6`

Bình luận (0)
TT
Xem chi tiết
KT
9 tháng 4 2022 lúc 9:44

a: x=4/27-2/3=4/27-18/27=-14/27

b: =>3/4x-1/4x=1/6+7/3

=>1/2x=1/6+14/6=5/2

hay x=5

c: =>13/10x=7/2+5/2=6

=>x=13/10:6=13/60

d: (3x+2)(-2/5x-7)=0

=>3x+2=0 hoặc 2/5x+7=0

=>x=-2/3 hoặc x=-35/2

Bình luận (0)
QN
9 tháng 4 2022 lúc 6:58

a) x = 4/27 - 2/3

    x = -14/27

Bình luận (0)
NT
9 tháng 4 2022 lúc 7:05

a: x=4/27-2/3=4/27-18/27=-14/27

b: =>3/4x-1/4x=1/6+7/3

=>1/2x=1/6+14/6=5/2

hay x=5

c: =>13/10x=7/2+5/2=6

=>x=13/10:6=13/60

d: (3x+2)(-2/5x-7)=0

=>3x+2=0 hoặc 2/5x+7=0

=>x=-2/3 hoặc x=-35/2

Bình luận (0)
LL
Xem chi tiết
DK
27 tháng 8 2023 lúc 14:47

a, 2/5 + 3/4 : x = -1/2

3/4 : x = -1/2 - 2/5

3/4 : x = -9/10

x = 3/4 : -9/10

x = -5/6

Bình luận (0)
DK
27 tháng 8 2023 lúc 14:48

b, 5/7 - 2/3 . x = 4/5 

2/3 . x = 4/5 + 5/7

2/3 . x = 53/35

x = 53/35 : 2/3

x = 159/70

Bình luận (0)
DK
27 tháng 8 2023 lúc 14:49

c và d mình làm dược nhưng ko ghi được cái suy ra

Bình luận (0)
LL
Xem chi tiết
H24
19 tháng 5 2022 lúc 14:57

tách đi bạn

Bình luận (0)
H24
19 tháng 5 2022 lúc 15:11

a) (2x - 3)(6 - 2x) = 0

=> \(\left[{}\begin{matrix}2x-3=0\\6-2x=0\end{matrix}\right.=>\left[{}\begin{matrix}2x=3\\2x=6\end{matrix}\right.=>\left[{}\begin{matrix}x=\dfrac{3}{2}\\x=3\end{matrix}\right.\)

b) \(5\dfrac{4}{7}:x=13=>\dfrac{39}{7}:x=13=>x=\dfrac{39}{7}:13=>x=\dfrac{3}{7}\)

c) \(2x-\dfrac{3}{7}=6\dfrac{2}{7}=>2x-\dfrac{3}{7}=\dfrac{44}{7}=>2x=\dfrac{47}{7}=>x=\dfrac{47}{14}\)

d) \(\dfrac{x}{5}+\dfrac{1}{2}=\dfrac{6}{10}=>\dfrac{x}{5}=\dfrac{6}{10}-\dfrac{1}{2}=>\dfrac{x}{5}=\dfrac{1}{10}=>x.10=5=>x=\dfrac{1}{2}\)

e) \(\dfrac{x+3}{15}=\dfrac{1}{3}=>\left(x+3\right).3=15=>x+3=5=>x=2\)

 

Bình luận (0)
NH
27 tháng 8 2023 lúc 12:55

f)\(\dfrac{x-12}{4}=\dfrac{1}{2}=\dfrac{x-12}{4}=\dfrac{2}{4}\)

\(x-12=2\)

   \(x=2+12\)

  x = 14

g)2\(\dfrac{1}{4}.\left(x-7\dfrac{1}{3}\right)=1,5\)

\(\dfrac{9}{4}.\left(x-\dfrac{22}{3}\right)=1,5\) 

      \(\left(x-\dfrac{22}{3}\right)=\dfrac{3}{2}:\dfrac{9}{4}\)

       \(x-\dfrac{22}{3}=\dfrac{2}{3}\)

       \(x=\dfrac{2}{3}+\dfrac{22}{3}\) 

      \(x=8\)

Bình luận (0)
NT
Xem chi tiết
NH
9 tháng 5 2022 lúc 21:14

a) \(\dfrac{2}{7}\times\dfrac{4}{3}+\dfrac{2}{6}\)

\(=\dfrac{8}{21}+\dfrac{2}{6}\)

\(=\dfrac{5}{7}\)

 

b) \(\dfrac{4}{7}:2+\dfrac{4}{7}\)

\(=\dfrac{2}{7}+\dfrac{4}{7}\)

\(=\dfrac{6}{7}\)

 

c) \(\dfrac{1}{3}+\dfrac{3}{4}-\dfrac{1}{5}:\dfrac{2}{3}\)

\(=\dfrac{13}{12}-\dfrac{3}{10}\)

\(=\dfrac{47}{60}\)

Bình luận (0)
IK
9 tháng 5 2022 lúc 21:14

\(\dfrac{8}{21}+\dfrac{2}{6}=\dfrac{16}{42}+\dfrac{14}{42}=\dfrac{30}{42}=\dfrac{5}{7}\)

\(b\) \(\dfrac{4}{7}\times\dfrac{1}{2}+\dfrac{4}{7}=\dfrac{2}{7}+\dfrac{4}{7}=\dfrac{6}{7}\)

\(c\) \(\dfrac{1}{3}+\dfrac{3}{4}-\dfrac{1}{5}\times\dfrac{3}{2}=\dfrac{1}{3}+\dfrac{3}{4}-\dfrac{3}{10}=\dfrac{20}{60}+\dfrac{45}{60}-\dfrac{18}{60}=\dfrac{47}{60}\)

Bình luận (0)
H24
9 tháng 5 2022 lúc 21:16

a) \(\dfrac{2}{7}\times\dfrac{4}{3}+\dfrac{2}{6}=\dfrac{8}{21}+\dfrac{2}{6}=\dfrac{16}{42}+\dfrac{14}{42}=\dfrac{30}{42}=\dfrac{5}{7}\)

b) \(\dfrac{4}{7}:2+\dfrac{4}{7}=\dfrac{4}{7}\times\dfrac{1}{2}+\dfrac{4}{7}=\dfrac{2}{7}+\dfrac{4}{7}=\dfrac{6}{7}\)

c) \(\dfrac{1}{3}+\dfrac{3}{4}-\dfrac{1}{5}:\dfrac{2}{3}=\dfrac{1}{3}+\dfrac{3}{4}-\dfrac{1}{5}\times\dfrac{3}{2}=\dfrac{1}{3}+\dfrac{3}{4}-\dfrac{3}{10}=\dfrac{20}{60}+\dfrac{45}{60}-\dfrac{18}{60}=\dfrac{20+45-18}{60}=\dfrac{47}{60}\)

Bình luận (0)
CV
Xem chi tiết
KR
18 tháng 8 2023 lúc 11:10

`#040911`

`a)`

`3 1/3 x + 16 3/4 = -13,25`

`=> 3 1/3 x = -13,25 - 16 3/4`

`=> 3 1/3 x = -30`

`=> x = -30 \div 3 1/3`

`=> x =-9`

Vậy, `x = -9`

`b)`

`3 2/7*x - 1/8 = 2 3/4`

`=> 3 2/7x = 2 3/4 + 1/8`

`=> 3 2/7x = 23/8`

`=> x = 23/8 \div 3 2/7`

`=> x = 7/8`

Vậy, `x = 7/8`

`c)`

`x \div 4 1/3 = -2,5`

`=> x = -2,5 * 4 1/3`

`=> x = -65/6`

Vậy, `x = -65/6`

`d)`

`( (3x)/7 + 1) \div (-4) = (-1)/28`

`=> (3x)/7 +1 = (-1)/28 * (-4)`

`=> (3x)/7 + 1 = 1/7`

`=> (3x)/7 = 1/7 - 1`

`=> (3x)/7 = -6/7`

`=> 3x = -6`

`=> x = -6 \div 3`

`=> x = -2`

Vậy, `x = -2.`

Bình luận (0)
H24
18 tháng 8 2023 lúc 11:05

a

=>10/3 . x + 16 + 3/4 = -13,25

=>10/3 x + 3/4 = -29,25

=>10/3 x = -30

=>x=-30 : 10/3

=>x=-30 . 3/10

=>x=-9

b.

=>23/7 x - 1/8 = = 11/4

=>23/7 x = 11/4 + 1/8

=>23/7 x= 22/8 + 1/8

=>23/7 x= 23/8

=>x=23/8 : 23/7

=>x=23/8 . 7/23

=>x=7/8

c.

=>x : 13/3 =-5/2

=>x=-5/2 . 13/3

=>x=-65/6

d.

=>3x/7 +1 = (-1/28) . (-4)

=>3x/7 + 1 = 1/7

=>3x/7 = -6/7

=>3x=-6

=>x=-2

Bình luận (0)
H9
18 tháng 8 2023 lúc 11:05

a) \(3\dfrac{1}{3}x+16\dfrac{3}{4}=-13,25\)

\(\Rightarrow\dfrac{10}{3}x+\dfrac{67}{4}=-\dfrac{53}{4}\)

\(\Rightarrow\dfrac{10}{3}x=-30\)

\(\Rightarrow x=-30:\dfrac{10}{3}\)

\(\Rightarrow x=-9\)

b) \(3\dfrac{2}{7}x-\dfrac{1}{8}=2\dfrac{3}{4}\)

\(\Rightarrow\dfrac{23}{7}x-\dfrac{1}{8}=\dfrac{11}{4}\)

\(\Rightarrow\dfrac{23}{7}x=\dfrac{11}{4}+\dfrac{1}{8}\)

\(\Rightarrow\dfrac{23}{7}x=\dfrac{23}{8}\)

\(\Rightarrow x=\dfrac{23}{8}:\dfrac{23}{7}\)

\(\Rightarrow x=\dfrac{7}{8}\)

c) \(x:4\dfrac{1}{3}=-2,5\)

\(\Rightarrow x:\dfrac{13}{3}=-\dfrac{5}{2}\)

\(\Rightarrow x=-\dfrac{5}{2}\cdot\dfrac{13}{3}\)

\(\Rightarrow x=-\dfrac{65}{6}\)

d) \(\left(\dfrac{3x}{7}+1\right):\left(-4\right)=\dfrac{-1}{28}\)

\(\Rightarrow\dfrac{3x}{7}+1=\dfrac{-1}{28}\cdot-4\)

\(\Rightarrow\dfrac{3x}{7}+1=\dfrac{1}{7}\)

\(\Rightarrow\dfrac{3x}{7}=-\dfrac{6}{7}\)

\(\Rightarrow x=-\dfrac{6}{7}:\dfrac{3}{7}\)

\(\Rightarrow x=-2\)

Bình luận (0)